Participatory Demonstration of Grass Strips as Biological Soil and Water Conservation Measures in Kamba Woreda, South Ethiopia - Yenealem Gemi; Amare Gojjam; Tademe Minase; Dagnaw Ademe; Birhanu Wolde (International Journal of Land, 2024)
Land degradation due to soil erosion and soil fertility depletion is a significant threat to the agricultural system, limiting food security and sustainable agricultural production. This study demonstrated Desho grass strips as biological soil and water conservation measures in Kamba woreda Gamo zone south Ethiopia. Six (6) nearby trial farmers who took part in the demonstration directly were chosen for the study using the purposive sample technique. Sole maize and integrated Desho grass strip with maize have been demonstrated on the trial farmers land having plot size of 4x12. Focus group discussions with farmers’ research extension group members have been carried out to determined farmers’ perception on the effect of Desho grass strip. The gathered information was examined using both descriptive and inferential statistics. The study's findings indicate that all metrics showed a significant difference (P < 0.05) between the treatments. When compared to sole maize, integrated grass strip with maize produced higher grain yields. The study revealed integrated grass strip with maize has 33.14% of yield advantage over sole maize. Additionally, the biomass result from harvested desho grass indicates an improvement with each harvesting cycle. Moreover, the result from focus group discussions shows, Desho grass strip has an effect on improving soil moisture, crop productivity, reducing soil erosion, and trials farmers have benefited economically having access to more feed for their animals by cut and carry system. Hence, the farmer’s first preference was implementing desho grass strip on their farm land by evaluating it with different criteria’s. The study concluded that, integrated Desho grass strips with maize has plays vital role for biological soil and water conservation measures and yield increment. Therefore, planting maize incorporating with biological soil amendments and water-saving techniques to improve maize yields and needs to popularize the investigation in large scale to reach the wider community.
Keywords: Biological; Grass strips; Soil Moisture; maize yields; perception